Mapeamento e análise da matrícula de estudantes com deficiência em três Universidades públicas brasileiras - Martins, Sandra Eli Sartoreto de Oliveira [UNESP]; Leite, Lúcia Pereira [UNESP]; Ciantelli, Ana Paula Camilo [UNESP] (My University, 2018)
The enrollment of students with disabilities in Higher Education is becoming more and more present in the Brazilian reality, however, it is difficult to draw a more realistic picture about the number of these students and their educational demands. This text critically portrays the graduation rates of students with disabilities in three public higher education institutions in the country. It is a longitudinal study that considered the procedures adopted in the identification of the entry and stay of these students, in the period of 2014-2015, raised by the consultation of the documentation of the institutions. The profile of graduates with disabilities, regarding the characterization and the form of self-declaration of the deficiencies instituted in the universities. It was noticed that the number of registrations is still timid, demonstrating the need for investments in affirmative and institutional policies, to guarantee the participation of this segment in the public university.
Mapping and analysis of the enrollment of students with disabilities in three Brazilian public universities
Keywords: Higher education; Inclusive education; People with disabilities